0982 Decide2Rest: A Program for Promoting Person-centered Obstructive Sleep Apnea (OSA) Treatment. (12th April 2019) - Fung, Constance H; Martin, Jennifer L; Liang, Li-Jung; Hays, Ron D; Col, Nananda; Zeidler, Michelle R; Patterson, Emily S; Josephson, Karen R; Huang, Yu-Chuang (David); Dzierzewski, Joseph M; Song, Yeonsu; Mitchell, Michael N; et al.
Abstract: Introduction: Person-centered care is a collaborative approach that is respectful of, and responsive to an individual's priorities, goals, needs, and values. For obstructive sleep apnea (OSA), this includes informing patients of their treatment options and actively engaging them in treatment decisions so that the treatment plan reflects what matters most to them. This approach is particularly relevant to care of patients with multimorbidity, which increases in prevalence with advanced age. We developed and evaluated a program that promotes person-centered OSA care for older adults. Methods: Patients with newly-diagnosed OSA were recruited from a Department of Affairs (VA) or university clinic and randomized to the Decide2Rest (D2R) program versus an attention control condition. D2R, a web-based program administered prior to a clinic appointment, provides information about OSA and treatment options, including the risks and benefits of each option. In an accompanying D2R paper workbook, participants list the treatment features that matter most to them, rate their overall health goals, and identify their preferred treatment. The program encourages patients to discuss their preferred treatment with their provider. Outcomes assessed post-intervention included the Decisional Conflict Scale (DCS; 0 [good] to 100 [bad]), which measures perceptions of uncertainty, whether decisions reflect what matters most to patients, and whether patients feel supported in decision making, and the Preparation for Decision Making (PDM; 0 [bad] to 100 [good]) scale. We used fixed-effects models to examine the relationship between D2R and study outcomes (DCS, PDM). Results: 73 patients (mean age 69 years [range: 60-89]; 71% male; N=37 VA, N=36 university site) were randomized to the D2R program (N=36) versus control condition (N= 37). Results from the fixed-effects models, controlling for study site, indicated that the D2R program showed a significantly lower Decisional Conflict Scale scores in treatment versus control (p=.014) and more favorable scores on the Preparation for Decision Making Scale (p<.001). Conclusion: The D2R Program promotes person-centered OSA decision-making for older adults with newly-diagnosed OSA. Future studies are needed to optimize implementation of the program. Support (If Any): NIA K23AG045937, AFAR, Hartford Foundation, Atlantic Philanthropies